Capital adequacy regulation and financial conglomerates - Ville Mälkönen (Bank of Finland, 2004)
A topical concern in public-policy debate is that the current capital adequacy regulation designed for stand-alone financial institutions exhibits several weaknesses due to the emergence of large financial institutions combining several activities under common control.This paper addresses these concerns using a theoretical framework derived from the economic literature.I will first describe the possible causes of the emergence of financial conglomerates, proceed to consider the theoretical background for the regulation of financial institutions, especially insurance and banking companies, and, finally, examine the limitations of the current regulatory framework in controlling the risks in financial conglomerates.My conclusions provide little support for the view that the regulatory approach should be modified towards a more consolidated one (ie harmonization).
URN:NBN:fi:bof-20140807167
Keywords: G21; G22; G28; 330; banking; capital adequacy regulation; insurance; financial conglomerates